DNA Methylation and Demethylation in Mammals - Chen, Zhao-xia (American Society for Biochemistry and Molecular Biology, 2011)
Cell type-specific DNA methylation patterns are established during mammalian development and maintained in adult somatic cells. Understanding how these patterns of 5-methylcytosine are established and maintained requires the elucidation of mechanisms for both DNA methylation and demethylation. The enzymes involved in the de novo methylation of DNA and the maintenance of the resulting methylation patterns have been fairly well characterized. However, important remaining challenges are to understand how DNA methylation systems function in vivo and in the context of chromatin. In addition, the enzymes and mechanisms for demethylation remain to be elucidated. There is still no consensus as to how active enzymatic demethylation is achieved in mammalian cells, but recent studies implicate base excision repair for genome-wide DNA demethylation in germ cells and early embryos.